(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Casting is one of the most important processes in manufacturing, as it allows for the production of complex parts with intricate shapes. It involves creating intricate patterns and shapes using sand as a medium. Sandcasting has been used to create beautiful artwork, jewelry, and architectural elements. It is a unique way to express creativity and can be used to make stunning pieces of art. The critical issue with the sand casting process is casting defects and unstable casting quality. The pulley’s quality characteristics have been affected by casting defects, which leads to a large number of shop floor trails, a high rejection rate, and poor casting performance. Knowledge of casting defects and causes is essential for quality control. Various researchers have stated that 90% of casting defects are obtained only because of the inadequate design of the gating and feeding systems. In this work, creo software was used to create the Solid model of a pulley and the gating system. Using Procast Simulation software, mold filling, and solidification analysis was performed. Medium carbon steel was chosen for its wide variety of automotive applications. The Sand mold was chosen as a mold material, and prediction analysis has been carried out using computer-aided simulation software.